„Synu mój najmilszy…”. Życie i edukacja Stanisława Mikołaja z Lubomirskich Tretera w latach 1776–1789, opisane przez ojca w trzynastu listach - Kowalczyk, Małgorzata Ewa (Biuletyn Historii Wychowania, 2011)
The author of the article presents the contents of an interesting treaty written in November 1785 in a mansion house in Mikołajów—situated in the Sandomierz area – by Stanisław Treter of the Lubomirskis (1744–1833), the chamberlain of the King Stanisław August Poniatowski. The purpose of the treaty was the presentation of life and education of his son Stanisław Mikołaj (1776–1861). The work devoted and dedicated to his, then nine-year-old, son, was written in a form of letters, very popular in the period of the Enlightenment. The letters are an interesting contribution to the history of upbringing, education, fatherhood, motherhood, childhood, travel and even medicine. They are a specific “voice of the epoch” reflecting the lifestyle, values, concerns and joys of the people of the Polish Enlightenment.